Dominant currencies and the export supply channel - Erik Frohm (European Central Bank (ECB), 2021)
Dominant currency pricing (DCP) weakens the demand-side effects of exchange rate changes on exports (Gopinath et al., 2020). However, adjustment in the export sector can still occur through other supply-side channels. With bilateral trade data at the HS2-product level, panel fixed-effects regressions and an instrumental variables (IV) approach, this paper presents several novel findings: (1), a depreciation of an exporter's currency against the US-dollar increases total export volumes between non-US countries, whereas bilateral exchange rates matter very little. (2), there is no statistically significant increase in average exports per firm (the intensive margin), while the aggregate export response is mainly driven by an increase in the number of exporting firms (the extensive margin). (3), there is substantial heterogeneity in the export response to exchange rates against dominant currencies. Market concentration, approximated by theHerfindahl-Hirschman Index (HHI), reduces the response of both the extensive and intensive margins to the US-dollar exchange rate. These results highlight an "export supply channel" of exchange rates in a world with dominant currencies, deepen our understanding of aggregate export adjustment and further underline the heterogeneous export response in different sectors to exchange rate changes.
Keywords: F14; F31; F41; 330; Exchange rates; dominant currencies; extensive margins of trade; intensive margins of trade; export heterogeneity